AB0928 Psoriatic arthritis and biologic therapy: Treatment response, drug survival and outcome after switching – an observational study. (23rd January 2014) - Wallis, D.; Jadon, D.; Tillett, W.; Waldron, N.; Cavill, C.; McHugh, N.; Korendowych, E.
Abstract : Background: Data on longer term efficacy and tolerance of biologic therapies in psoriatic arthritis (PsA) are emerging. Persistence with the first TNF inhibitor (TNFi) at one year is estimated at 70-87%. Data on the benefit of switching between TNFi are limited but persistence with a second agent at one year is reported as 74-81%. Objectives: To investigate the treatment response, drug survival and outcome with the first and subsequent biologic agents in patients with PsA. Methods: Data were collected from a prospective single-centre cohort of PsA patients who were started on a biologic agent between 1st Jan 2003 – 1st Sept 2010. Results: Seventy-one patients started a biologic agent of whom 96% had polyarticular disease. The median follow-up was 36 months, median age at start of biologic 47y and median disease duration 10y. The most frequently prescribed first biologic agent was etanercept (58%) followed by adalimumab (35%) and infliximab (7%). Thirty-six percent started a biologic agent as monotherapy, 49% started in combination with one DMARD and 13% with two DMARDs. Ninety-six percent fulfilled the Psoriatic Arthritis Response Criteria (PsARC) where completed. Persistence with the first biologic was 92% at 6 months, 87% at 12 months, 74% at 24 months and 70% at 36 months. Six patients (8.4%) stopped due to secondary inefficacy (after 12 weeks) and 16 (23%) stopped due to an adverse event. Nineteen patients switched to a second biologic agent (6 due to secondary inefficiency and 13 due to an adverse event). Persistence was 67% at 6 months and 53% at 12 months. One patient stopped due to primary inefficacy, 2 due to secondary inefficacy and 7 had an adverse event. Of the 6 patients who had switched to a second agent because of secondary inefficacy, one continued on the second agent, one switched again because of primary inefficacy, 2 switched again because of secondary inefficacy and 2 switched again because of an adverse event. Of the 13 patients who switched to a second agent because of an adverse event, 8 continued on the second agent, one stopped biologic therapy and 3 switched again because of an adverse event. One patient was pending switch to a 3rd biologic at the time of analysis. Eight patients switched to a third biologic. Six continued on the third agent (median follow up after switching 26 months). Two switched to a 4th agent (ustekinumab) because of secondary inefficacy and remained on the 4th agent at 4 and 11 months follow up respectively. Median percentage improvements with the first biologic at 12 and 24 months respectively were 79% and 100% in swollen joint count, 77% and 83% in tender joint count, 50% and 56% in Health Assessment Questionnaire, 67% and 61% in Psoriasis Area and Severity Index, 89% and 100% in Dermatology Life Quality Index and 100% and 100% in the Bath Nail Score. Conclusions: Persistence with the first biologic agent in this cohort was 87% at 12 months, 74% at 24 months and 70% at 36 months. The response to the first biologic agent was sustained at 24 months across joint, skin, nail and quality of life measures. Persistence with the second biologic agent was 53% at 12 months. Patients who switched to a second biologic agent because of adverse event were more likely to continue with the second agent than those who switched because of secondary inefficacy. Disclosure of Interest: D. Wallis Grant/Research support from: The work was partly supported by an unrestricted research grant from Abbott Laboratories, D. Jadon: None Declared, W. Tillett: None Declared, N. Waldron: None Declared, C. Cavill: None Declared, N. McHugh: None Declared, E. Korendowych: None Declared